Feasibility of Integration of Yoga in a Behavioral Weight‐Loss Intervention: A Randomized Trial. Issue 3 (2nd February 2021) - Jakicic, John M.; Davis, Kelliann K.; Rogers, Renee J.; Sherman, Sally A.; Barr, Susan; Marcin, Marissa L.; Collins, Katherine A.; Collins, Audrey M.; Yuan, Nalingna; Lang, Wei
Abstract : Objective: This study examined the feasibility and comparison of two styles of yoga within the context of a standard behavioral weight‐loss intervention (SBWI). Methods: Fifty adults with obesity (BMI: 31.3 ± 3.8 kg/m 2 ) participated in this 6‐month study that included a SBWI and a calorie‐ and fat‐reduced diet. Randomization was to restorative Hatha (SBWI+RES) or Vinyasa (SBWI+VIN) yoga. Yoga was prescribed to increase from 20 to 40 to 60 minutes per session across the intervention. Weight was assessed at baseline and 6 months. Perceptions of yoga were assessed at the completion of the intervention. Results: Adjusted weight loss was −3.4 kg (95% CI: −6.4 to −0.5) in SBWI+RES and −3.8 kg (95% CI: −6.8 to −0.9) in SBWI+VIN ( P  <   0.001), with no difference between groups. Of all participants, 74.4% reported that they would continue participation in yoga after the SBWI. Session duration was a barrier as yoga increased from 20 to 40 to 60 minutes per day, with 0%, 7.5%, and 48.8% reporting this barrier, respectively. Conclusions: Among adults with obesity, yoga participation, within the context of a SBWI, appears to be feasible, with weight loss not differing by style of yoga. Progressing to 60 minutes per session appears to be a barrier to engagement in yoga in this population.